Procedimento para avaliação do impacto da compensação reativa shunt capacitiva na estabilidade de tensão - Luiz Mariano Junior (2008)
This work proposes a procedure to evaluate the impact of the Reactive Shunt Capacitive Compensation on Power System Voltage Stability. The procedure is related to Expansion Activities and aims to support planning decision process in order to increase system security to avoid voltage instability phenomenon. Reactive shunt capacitive compensation is widely applied on power systems due to several positive aspects. Among others, it provides better system voltage profile, power factor correction, power loss decrease and better exploitation of system network. Additionally, it presents low cost and simple implementation. However, the addition of this type of compensation on system network increases the bus voltage value at the maximum loading point, that may causes problems relative system voltage stability. The approximation of this dangerous condition to the usually adopted voltage operative limits must be hardly avoided. So, the decision about the inclusion of a new system compensation requires very detailed analyses. The methodology implemented in this thesis identifies adequate system compensation and is structured in two modules. The former prepares a bus ranking to receive reactive compensation, and the later points maximum compensation values to avoid system voltage instability.